Parenting sensitivity, salivary oxytocin levels and children’s behavioral problems in a Portuguese sample - Torres,Nuno (2022)
Abstract The present study focused on the quality of parenting behaviors (sensitivity and intrusiveness), its associations with children's levels of oxytocin (OXT), and with children's behavioral problems in the preschool context. Thirty nuclear families, including both parents and one focal child, and their preschool teachers participated in the study. Salivary OXT was collected (during two separate home visits) from children after a play task with each parent. Sensitivity and intrusiveness were coded based on the videotapes of these dyadic play interactions. Preschool teachers reported children’s behavioral problems using the Caregiver-Teacher Report Form. Salivary OXT was collected by passive drooling, and quantified by radioimmunoassay, after extraction. Results show that only fathers’ sensitivity and intrusiveness were significantly correlated with children’s OXT concentrations. Both mothers’ and fathers’ sensitivity were negatively correlated with children’s internalizing problems. Mothers’ intrusiveness was positively correlated with children’s externalizing problems, and fathers’ intrusiveness with children’s internalizing problems.